Bio-Inspired Secure Routing in IoT-Enabled Smart Healthcare Networks - Rambabu, Bandi; Adudhodla, Mallareddy; Archana, M; Reddy, K Deepthi; Swathi, Vnvls (2025 3rd International Conference on Sustainable Computing and Data Communication Systems (ICSCDS), 2025)
The integration of Internet of Things in smart healthcare has introduced complex challenges in routing, where ensuring secure, energy-efficient, and low-latency data transmission is paramount. Traditional algorithms often fall short in addressing dynamic network conditions and emerging security threats. This research proposes a novel hybrid routing framework that synergizes the Adaptive Artificial Bee Colony (AABC) algorithm with a lightweight blockchain architecture to enhance routing intelligence and data security in IoT-enabled healthcare environments. The AABC algorithm dynamically optimizes routing paths based on energy, trust, and link quality metrics, while the blockchain layer provides decentralized trust management, immutable audit trails, and secure authentication with minimal resource overhead. To validate its effectiveness, the proposed method is benchmarked against three recent algorithms-Trust-based Secure Routing Protocol, Firefly Algorithm-based Secure Routing, and Quantum-Inspired Ant Colony Optimization. Simulation results demonstrate that this hybrid approach achieves a 10% higher packet delivery ratio, reduces end-to-end delay by 22.7%, and extends network lifetime by 29%, outperforming the comparative models across all key performance metrics. Furthermore, it exhibits resilience against common routing attacks such as blackhole and sinkhole, affirming its robustness. The proposed solution offers a scalable and secure routing paradigm well-suited for next-generation, mission-critical IoT healthcare systems.